Das Abwandern parasitierter Aphiden von ihren Wirtspflanzen und eine Methode zu ihrer Erfassung. - Behrendt, Kurt (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Mummies of aphids often occur in other places than the sucking places of the parasitized aphids. The last larval instar of Aphelinus chaonia (Walker) provokes the attacked Aphis fabae regularly to migrate from the colony and usually from the plant. This praemummy comes to rest by thigmotactic stimuli before being mummified. In laboratory rearing also Aphelinus asychis (semiflavus) (Walker) preferably shows this behaviour on Myzus persicae Sulzer and Aphis fabae Scopoli . With the aphidiids Lysiphlebus fabarum (Marshall), Ephedrus plagiator (Nees), Praon abjectum (Haliday), Trioxys angelicae (Haliday), this migration of the hosts as praemummies is connected with diapause (under conditions of a 8hort day) or partially with aestivation (under conditions of a long day). As a rule the parasites emerge without delay only from aphids which are mummified in their sucking places. This migration in the open air can be demonstrated by putting rings made of rubber sponge round the parts of plants that are attacked by aphids. On Evonymus europaea as a main host of Aphis fabae the catch of mummies was several times bigger on the rings than on the foliage. By this method Aphelinus chaonia was established as a species very much in evidence around Eberswalde near Berlin.